Pengaruh Lingkungan Kerja Non Fisik Dan Beban Kerja Terhadap Kinerja Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pegawai Dinas Pemadam Kebakaran - Elias Binosa Nopecain; Tan Evan Tandiyono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to prove and analyze the influence of non-physical work environment and workload have a significant effect on employee performance and job satisfaction at the Surabaya II Rayon Fire and Rescue Service; as well as to prove and analyze Job satisfaction has a significant effect on the performance of the Surabaya II Rayon Fire and Rescue Service employees. This type of research used is quantitative research. How to collect data using a questionnaire and using a Likert scale as an answer. Sampling using saturated samples and PLS as analytical tools. Source of data used is primary data. The sample population is the Surabaya II District Fire and Rescue Service employees. Based on the results of data analysis, it shows that the Non-Physical Work Environment has a significant effect on Employee Performance and Job Satisfaction at the Surabaya II Rayon Fire and Rescue Service; and Workload has no significant effect on Employee Performance, but Workload has a significant effect on Job Satisfaction of employees of the Surabaya II Rayon Fire and Rescue Service; and Job Satisfaction has a significant effect on Employee Performance at the Surabaya II Rayon Fire and Rescue Service. The advice given in this study, in order to increase Job Satisfaction, refers to previous research that by improving the Non-Physical Work Environment and Workload will increase Job Satisfaction and by improving organizational culture, work motivation and job satisfaction that occur, the performance of the Fire Department employees and Rescue Rayon Surabaya II, and are expected to be able to add or develop other variables apart from the variables used in this study which are thought to affect employee performance such as promotion, leadership, and others.